Polyimide-based dielectric heat-conducting composite material and preparation method thereof
By using modified boron nitride nanosheets and nanosilver wires as thermal conductivity fillers in the polyimide matrix, and by electrospinning and electrostatic spraying technology, combining hot pressing and thermal imidation treatment, polyimide-based dielectric thermal conductivity composite materials with high thermal conductivity and low dielectric properties are prepared, which solves the problems of insufficient thermal conductivity and reduced mechanical properties of existing materials, and achieves efficient thermal management and low dielectric properties.
Patent Information
- Application Number
- CN202311337472.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
The thermal conductivity of the existing polyimide-based thermal conductivity composite materials is insufficient, and the high content of fillers leads to a decrease in mechanical properties, making it difficult to meet the high thermal conductivity and low dielectric properties while improving.
Polydopamine-modified boron nitride nanosheets (MBN) and nanosilver wires (AgNW) were used as thermal conductivity fillers. The MBN was distributed in polyamic acid (PAA) nanofibers by electrospinning technology, and AgNW was electrostatically sprayed, combined with hot pressing and thermal imidation treatment, and polyimide-based dielectric thermal conductivity composite materials with high thermal conductivity and low dielectric properties were prepared.
The thermal conductivity of the composite material has been significantly improved, reaching a maximum of 8.38W/mK, while maintaining high insulation and low dielectric constant, and the volume resistivity is much higher than the standard of insulating materials.
Smart Images

Figure CN119840265A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermally conductive composite materials, and in particular to a polyimide-based dielectric thermally conductive composite material and a preparation method thereof. Background Art
[0002] With the trend of miniaturization of microelectronic packaging, the continuous increase in power consumption has put forward more stringent requirements for thermal management, which is crucial to ensure the performance, reliability and extend the service life of electronic systems. However, in addition to high thermal conductivity, these materials need to meet additional requirements for practical applications. Especially in the field of 5G, low dielectric properties can reduce signal delay, crosstalk and power consumption. Excellent electrical insulation properties are also urgently needed to prevent short circuits. Polyimide (PI) has the advantages of good electrical insulation, high mechanical strength, good chemical resistance, good thermal stability and low dielectric properties, and has been widely used in electronic packaging. However, the intrinsic thermal conductivity of pure PI is as low as 0.1-0.4W / mK, which is far from meeting the requirements of the thermal conductivity industry, so it is necessary to introduce thermal conductive fillers into the PI matrix, such as carbon nanotubes, graphene oxide, ceramic oxides and nitrides. Among them, boron nitride (BN) is one of the outstanding candidate materials for the preparation of high thermal conductivity composite materials due to its excellent electrical insulation, high thermal stability and low dielectric constant. Although the thermal conductivity of filled composite materials increases with the increase of fillers, high content of fillers leads to reduced mechanical properties of composite materials. In addition, directly mixing fillers into the PI matrix will only increase the thermal conductivity of composite materials to a limited extent. Therefore, it is very important to use fillers efficiently and maximize their effect on improving thermal conductivity. Summary of the invention
[0003] In view of the shortcomings and deficiencies of the prior art, the present invention uses polyimide (PI) as a polymer matrix, selects polydopamine-modified boron nitride nanosheets (MBN) and nano silver wires (AgNW) as nano hybrid thermal conductive fillers, uses electrostatic spinning technology to orient MBN in polyamic acid (PAA) nanofibers, and electrostatically sprays AgNW dispersion, then laminates and hot presses the nanofibers, and finally thermally imidizes them to prepare a polyimide-based dielectric thermal conductive composite material. The method can regulate the spinning structure, has the characteristics of simple operation, strong controllability, and easy promotion of large-scale production.
[0004] To this end, the technical solution of the present invention is as follows:
[0005] 1) BN stripping: Commercial BN powder is placed in a mixed solution of alcohol / water in a predetermined ratio, and BN is stripped with the aid of ultrasound. After the ultrasonic stripping is completed, the obtained BN suspension is centrifuged to remove the unstripped multilayer BN to prepare a BN nanosheet (BNNS) suspension, which is then filtered and dried.
[0006] Furthermore, the primary alcohol solvent may be ethanol, isopropanol, butanol, or amyl alcohol.
[0007] Furthermore, the ultrasonic treatment time is 5 to 12 hours, and the ultrasonic temperature is 20 to 30°C.
[0008] Furthermore, the speed of the centrifugal treatment is 2000-4000 r / min, and the time is 10-30 min.
[0009] Furthermore, the filtering device is a sand core suction filtration, and the filter membrane is a nylon organic membrane.
[0010] Furthermore, the drying temperature is 60 to 80° C. and the drying time is 4 to 10 hours.
[0011] 2) Modified BNNS: BNNS was modified by the polydopamine method. After adding BNNS to a tris-buffer ethanol buffer with a concentration of 10mM and a pH of 8.5 and ultrasonically dispersing, a corresponding proportion of dopamine hydrochloride was added for reaction. After the reaction, the excess dopamine was removed by washing with water and ethanol, and finally dried in an oven at 60°C for 12h to obtain MBN. Since dopamine is very easy to polymerize and can effectively adhere to any surface, it has strong adaptability in modified fillers.
[0012] Furthermore, the tris-buffer ethanol buffer solution with a pH value of 8.5 is prepared by mixing a tris-buffer buffer solution with a pH value of 8.5 and anhydrous ethanol in a mass ratio of 3:1.
[0013] Furthermore, the reaction time is 6 to 10 hours, and the reaction temperature is 25 to 60°C.
[0014] Furthermore, the feed ratio of BNNS to dopamine hydrochloride is 1:0.4.
[0015] 3) preparing a polyamic acid (PAA) solution: taking a certain proportion of the MBN prepared in step 2) and ultrasonically dispersing it in an organic solvent to obtain a suspension; in an inert atmosphere, in a three-necked flask equipped with a mechanical stirrer and a vent tube, first adding a diamine monomer to the suspension until it is completely dissolved; then adding a dianhydride monomer in batches while maintaining high-speed stirring and stirring evenly; reacting for a certain period of time in an ice-water bath to obtain a MBN / PAA solution.
[0016] Furthermore, the mass percentage of the MBN is 5-20wt%.
[0017] Furthermore, the organic solvent may be one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) or N,N-dimethylethanolamine (DMEA).
[0018] Furthermore, the inert atmosphere can be a mixture of one or more of nitrogen and argon, wherein the gas flow rate is 50 to 100 mL / min.
[0019] Furthermore, the diamine monomer may be one or a mixture of 4,4'-diaminodiphenyl ether (ODA), 4,4'-methylenedianiline (MDA), metaphenylenediamine (MPD), ethylenediamine (EDA), hexamethylenediamine (HDA) or 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFDB).
[0020] Furthermore, the dianhydride monomer may be one or a mixture of pyromellitic dianhydride (PMDA), 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (6FDA), biphenyltetracarboxylic dianhydride (BPDA), and 4,4'-oxydiphthalic acid (ODTA).
[0021] Furthermore, the dianhydride monomer is added in 4 batches, with an interval of 10-20 minutes between each batch. After each added dianhydride monomer is completely dissolved, the next batch of dianhydride monomer is added, and the amount added each time is half of the previous amount.
[0022] Furthermore, the mechanical stirring rate is 200-400 r / min, and the reaction time is 6-12 h.
[0023] Furthermore, the molar ratio of the diamine reactive monomer to the dianhydride reactive monomer is 1:1 to 1.05.
[0024] 4) Preparation of silver nanowire (AgNW) dispersion: After polyvinyl pyrrolidone (PVP) is dissolved in polyol, silver nitrate (AgNO3) is added until it is completely dissolved, and after a nucleating agent is dissolved in polyol, the mixed solution is added. After the solution is fully stirred, it is transferred to a round-bottom flask, heated to a specific temperature, and kept at this temperature for a certain period of time to obtain an AgNW stock solution; the AgNW stock solution is centrifuged, washed and purified to obtain AgNW; finally, the AgNW is dispersed in a mixed solution of water and ethanol for later use.
[0025] Furthermore, the polyol may be one of ethylene glycol, propylene glycol or glycerol.
[0026] Further, the nucleating agent may be one of KBr, NaCl or CuCl2, NaCl and NaBr, KCl and FeCl3.
[0027] Furthermore, the concentration of AgNO3 is 5-15 g / L, and the mass ratio of PVP to AgNO3 is 1:1 to 2:1.
[0028] Furthermore, the insulation temperature is 120-180°C and the insulation time is 30-120 minutes.
[0029] 5) The MBN / PAA solution is spun by an electrostatic spinning method, and AgNW is electrostatically sprayed at the same time to obtain a MBN-AgNW / PAA fiber membrane.
[0030] Furthermore, the voltage is 18-24 kV, the receiving distance is 15-25 cm, the speed of the receiving roller is 50-100 r / min, the ambient temperature is 25-35° C., and the ambient humidity is 20% to 50%.
[0031] 6) The MBN-AgNW / PAA fiber membrane was cut into small squares (4×4 cm), staggered and laminated, hot pressed, and finally subjected to thermal imidization treatment.
[0032] Furthermore, the hot pressing is performed at 270 to 300° C. and 15 to 20 MPa for 10 to 20 min.
[0033] Furthermore, the thermal imidization is carried out at 300° C. for 1 hour.
[0034] The present invention has the following advantages and beneficial effects:
[0035] 1. In the present invention, the method of combining in-situ polymerization and electrostatic spinning is used to improve the dispersion of MBN in the matrix and realize the radial orientation of the thermal conductive filler along the nanofibers, which is helpful to construct the MBN thermal conductive network.
[0036] 2. In the present invention, the electrostatic spraying technology is used to take advantage of the high aspect ratio of AgNW to play its bridging role and construct a complete thermal conductive path in the non-contacting MBN, so that the polymer-based composite material can achieve high thermal conductivity at a lower content of thermal conductive filler, while the polymer-based composite material still retains high insulation.
[0037] 3. In the present invention, the thermal conductivity (λ) of the composite material is significantly improved, with a maximum value of 8.38 W / mK; the dielectric constant (ε) is also relatively low (ε<3.84); the volume resistivity is 2.40×10 14 Ωcm, which is much higher than the standard of insulating materials (1×10 9 Ω·cm). BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Fourier transform infrared spectra of BN before and after modification;
[0039] Figure 2 is the scanning electron microscope image of AgNW;
[0040] Figure 3 This is a scanning electron microscope photograph of the MBN-AgNW / PAA thermally conductive composite film obtained in Example 1;
[0041] Figure 4 This is a scanning electron microscope image of the pure PAA fiber membrane obtained in Comparative Example 1; DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0043] Example 1
[0044] 1) Exfoliation of boron nitride (BN): 100 mL of 1 g commercial BN powder was placed in a mixed solution of alcohol / water (volume ratio 1:1), and the mixture was ultrasonically crushed for 10 h using an ultrasonic cleaner. After the ultrasonic exfoliation was completed, the obtained BN suspension was centrifuged at 2000 rpm for 10 min to remove the unexfoliated multilayer BN. The upper layer was filtered with a nylon membrane filter (diameter 50 mm, pore size 0.1 μm), washed with deionized water 3 times to remove impurities, and then the product was dried in a vacuum oven at 60°C for 10 h to obtain BNNS.
[0045] 2) Modified BNNS: 0.4 g of BNNS powder was dispersed in 100 mL of 10 mM Tris-buffer ethanol buffer solution with a pH of 8.5, stirred evenly, and ultrasonicated for 2 h to fully disperse it. Then, 0.16 g of dopamine hydrochloride was added and stirred for reaction at 25 °C for 6 h. Then, it was filtered, washed alternately with deionized water and anhydrous ethanol, and then dried in an oven at 60 °C to obtain MBN.
[0046] 3) Prepare PAA solution: 5 wt% MBN prepared in step 2) was ultrasonically dispersed in DMF to obtain a suspension, and a series of MBN / PAA solutions were synthesized by in-situ polymerization. ODA was placed in a three-necked flask containing the above suspension and stirred at 0°C under nitrogen purge until ODA was completely dissolved. BPDA was added in 4 batches (the molar ratio of diamine to dianhydride monomer was 1:1.01). Each batch was added to the above system every 20 minutes and stirred for 12 hours to form a uniform viscous MBN / PAA solution.
[0047] 4) Preparation of AgNW dispersion: At room temperature, completely dissolve 0.2g PVP in 25mL EG. Add 0.25g AgNO3 to the mixed solution until it is completely dissolved. Then, add the nucleating agent (NaCl, NaBr) dissolved in EG to the above solution, stir evenly, raise the temperature to 170°C, and stir for 60 minutes. After the reaction, the prepared AgNW stock solution is centrifuged and washed and purified with deionized water and anhydrous ethanol for multiple times to obtain AgNW. Finally, AgNW is dispersed in a mixed solution of ethanol and water (volume ratio 1:1) for use, and the dispersion concentration is 5mg / mL.
[0048] 5) Preparation of fiber membrane: The MBN / PAA spinning solution and the AgNW dispersion were loaded into two syringes respectively by a method combining solution electrospinning and electrostatic spraying. The two syringes were fixed on two propellers. The spinning solution was electrospun at 30°C with an applied voltage of 20 kV, a spinning speed of 0.5 mL / h, a receiving roller speed of 50 r / min, a spinning distance of 20 cm, and an ambient humidity of 40%. The electrostatic spraying distance was 23 cm, the propulsion speed was 0.2 mL / h, and other conditions were consistent with electrospinning.
[0049] 6) The MBN-AgNW / PAA fiber membrane was cut into small squares (4×4 cm), stacked in an alternating manner, and then hot-pressed at 280°C, 20 MPa for 10 min, and finally heat-treated at 300°C for 1 h for thermal imidization.
[0050] like Figure 1 As shown in the figure, before BN modification, only the ions at 1376 and 804 cm -1 Two strong characteristic peaks appear at 1627cm -1 and 3429cm -1 Two characteristic peaks appear at , which are attributed to the stretching vibration of the aromatic ring and the hydroxyl group on PDA.
[0051] like Figure 2 As shown, the length of AgNWs is between 20 and 40 μm, and the average diameter is 100 nm.
[0052] Implementation effect: The λ of the MBN-AgNW / PI dielectric thermal conductive composite material is 2.29W / mK, ε is 3.05, and the volume resistivity is 2.92×10 14 Ωcm. Scanning electron microscope pictures are shown in Figure 3 As shown, MBN overlaps linearly and orderly along the fiber surface, and AgNW connects MBN and fibers to further improve the thermal conduction path.
[0053] Comparative Example 1
[0054] The difference between this comparative example and Example 1 is that no filler is added, no electrostatic spraying is performed, and the PAA solution obtained in step 3) is directly subjected to electrostatic spinning, and a PI film is obtained after hot pressing and thermal imidization.
[0055] Implementation effect: The λ of the prepared PI film is 1.9W / mK, ε is 2.76, and the volume resistivity is 3.01×10 14 Ωcm. SEM images of pure PAA membranes are shown in Figure 4 shown.
[0056] Comparative Example 2
[0057] The difference between this comparative example and Example 1 is that there is no electrostatic spraying, and the amount of MBN added in step 3) is 5 wt%.
[0058] Implementation effect: The λ of the prepared MBN / PI dielectric thermal conductive composite material is 2.13 W / m K.
[0059] Example 2
[0060] The difference between this embodiment and embodiment 1 is that the amount of MBN added in step 3) is 10 wt%.
[0061] Implementation effect: The λ of the MBN-AgNW / PI dielectric thermal conductive composite material is 4.14 W / m K, ε is 3.36, and the volume resistivity is 2.84×10 14 Ωcm.
[0062] Example 3
[0063] The difference between this embodiment and embodiment 1 is that the amount of MBN added in step 3) is 15 wt%.
[0064] Implementation effect: The prepared MBN-AgNW / PI dielectric thermal conductive composite material has a λ of 6.21 W / mK, an ε of 3.52, and a volume resistivity of 2.62×10 14 Ωcm.
[0065] Example 4
[0066] The difference between this embodiment and embodiment 1 is that the amount of MBN added in step 3) is 20 wt%.
[0067] Implementation effect: The prepared MBN-AgNW / PI dielectric thermal conductive composite material has a λ of 8.38 W / m K, an ε of 3.84, and a volume resistivity of 2.40×10 14 Ωcm.
[0068] Comparative Example 3
[0069] The difference between this comparative example and Example 1 is that there is no electrostatic spraying, and the amount of MBN added in step 3) is 10 wt%.
[0070] Implementation effect: The λ of the prepared MBN / PI dielectric thermal conductive composite material is 3.12 W / m K.
[0071] Comparative Example 4
[0072] The difference between this comparative example and Example 1 is that there is no electrostatic spraying, and the amount of MBN added in step 3) is 15 wt%.
[0073] Implementation effect: The λ of the prepared MBN / PI dielectric thermal conductive composite material is 4.79 W / m K.
[0074] Comparative Example 5
[0075] The difference between this comparative example and Example 1 is that there is no electrostatic spraying, and the amount of MBN added in step 3) is 20 wt%.
[0076] Implementation effect: The λ of the prepared MBN / PI dielectric thermal conductive composite material is 6.83 W / m K.
[0077] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned manner. As long as various improvements are made using the method concept and technical solution of the present invention, they are all within the protection scope of the present invention.
Claims
1. A polyimide-based dielectric thermally conductive composite material and a preparation method thereof, characterized in that The steps include: 1) Exfoliation-modified boron nitride (BN): commercial BN powder is placed in a mixed solution of alcohol / water in a predetermined ratio, and the boron nitride is exfoliated with the aid of ultrasound. After the ultrasonic exfoliation is completed, the obtained BN suspension is centrifuged to remove the unexfoliated multilayer BN, thereby preparing a BN nanosheet (BNNS) suspension, which is then filtered and dried; 2) BNNS was modified by the polydopamine (PDA) method. After adding BNNS to a tris-buffer ethanol buffer with a concentration of 10 mM and a pH of 8.5 and ultrasonically dispersing, a corresponding proportion of dopamine hydrochloride was added for reaction. After the reaction, the excess dopamine was removed by washing with water and ethanol, and finally the modified boron nitride nanosheets (MBN) were obtained by drying in an oven at 60°C for 12 h. 3) preparing a polyamic acid (PAA) solution: taking a certain proportion (0, 5, 10, 15, 20 wt%) of the MBN prepared in step 2) and ultrasonically dispersing it in an organic solvent to obtain a suspension, and protecting it with an inert atmosphere such as nitrogen or argon, in a three-necked flask equipped with a mechanical stirrer and a vent pipe, first adding a diamine monomer into the organic solvent until it is completely dissolved, and then adding a dianhydride monomer in 4 batches with a stirring speed of 200 to 400 r / min, with an interval of 10 to 20 minutes between each batch, and stirring evenly, and reacting in an ice-water bath for 6 to 12 hours to obtain a PAA solution; 4) After polyvinyl pyrrolidone (PVP) is dissolved in polyol, silver nitrate (AgNO3) is added until it is completely dissolved, and after the nucleating agent is dissolved in polyol, the mixed solution is added, the solution is fully stirred and transferred to a round-bottom flask, and the temperature is raised to 120-180°C and kept at this temperature for 30-120 minutes to obtain a silver nanowire (AgNW) stock solution; the AgNW stock solution is centrifuged, washed and purified to obtain AgNW; finally, the AgNW is dispersed in a mixed solution of water and ethanol for later use. 5) The MBN / PAA solution of step 3) is spun by electrospinning, and at the same time, the AgNW of step 4) is electrostatically sprayed to obtain a MBN-AgNW / PAA fiber membrane; the experimental parameters are as follows: voltage is 18-24 kV, receiving distance is 15-25 cm, the speed of the receiving roller is 50-100 r / min, the ambient temperature is 25-35°C, and the ambient humidity is 20% to 50%. 6) The MBN-AgNW / PAA fiber membrane in step 5) was cut into small squares (4×4 cm), and subjected to staggered lamination and hot pressing. Finally, a thermal imidization treatment was performed under vacuum and high temperature to obtain MBN-AgNW / PI.
2. The method for preparing a polyimide-based dielectric thermally conductive composite material according to claim 1, characterized in that: The alcohol solvent in step 1) can be ethanol, isopropanol, butanol, or amyl alcohol; the ultrasonic treatment time is 5 to 10 hours, and the ultrasonic temperature is 20 to 30° C.; the centrifugal treatment speed is 2000 to 4000 r / min, and the time is 10 to 30 minutes; the filtration device is a sand core filtration, and the filter membrane is a nylon organic membrane; the drying temperature is 60 to 80° C., and the time is 4 to 10 hours.
3. The method for preparing a polyimide-based dielectric thermally conductive composite material according to claim 1, characterized in that: The tris-buffer ethanol buffer solution with a pH value of 8.5 in step 2) is prepared by mixing a tris-buffer buffer solution with a pH value of 8.5 and anhydrous ethanol in a mass ratio of 3:1; the reaction time is 6 to 10 hours, and the reaction temperature is 25 to 60° C.; the feed ratio of BNNS to dopamine hydrochloride is 1:0.
4.
4. The method for preparing a polyimide-based dielectric thermally conductive composite material according to claim 1, characterized in that: In step 3), the diamine monomer can be a mixture of one or more of 4,4'-diaminodiphenyl ether (ODA), 4,4'-methylenedianiline (MDA), metaphenylenediamine (MPD), ethylenediamine (EDA), hexamethylenediamine (HDA) or 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFDB); the dianhydride monomer can be a mixture of one or more of pyromellitic dianhydride (PMDA), 4,4'-(hexafluoroisopropyl)diphthalic anhydride (6FDA), biphenyltetracarboxylic dianhydride (BPDA), 4,4'-oxydiphthalic acid (ODTA); the molar ratio of the diamine reaction monomer to the dianhydride reaction monomer is 1:1 to 1.
05.
5. The method for preparing a polyimide-based dielectric thermally conductive composite material according to claim 1, characterized in that: The organic solvent in step 3) can be one or a mixture of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) or N,N-dimethylethanolamine (DMEA).
6. The method for preparing the polyimide-based dielectric thermally conductive composite material according to claim 1, characterized in that: In step 4), the polyol may be one of ethylene glycol, propylene glycol or glycerol; the nucleating agent may be one of KBr, NaCl or CuCl2, NaCl and NaBr, KCl and FeCl3; the concentration of AgNO3 is 5-15g / L, and the mass ratio of PVP to AgNO3 is 1:1 to 2:
1.
7. The method for preparing the polyimide-based dielectric thermally conductive composite material according to claim 1, characterized in that: The hot pressing in step 6) is performed at 270-300° C. and 15-20 MPa for 10-20 min; Thermal imidization was carried out at 300°C for 1 h.
Citation Information
Patent Citations
Method for preparing silver nanowires
CN105537622A
Method for modifying boron nitride nanosheet surface with polydopamine
CN106554514A
Polydopamine modified boron nitride nanosheet / polyimide composite fiber heat-conducting film as well as preparation method and application thereof
CN116061525A
Scalable electrically conductive nanowires bundle-ring-network for deformable transparent conductor
US20210016349A1
Cited By
Preparation method of aramid nanofiber-based composite film with high thermal conductivity and breakdown resistance
CN121064510A
Preparation method of aramid nanofiber-based composite film with high thermal conductivity and high breakdown resistance
CN121064510B